Promoting the psychosocial well being of children following war and terrorism - Friedman, Matthew J.; Mikuš Kos, Anica (NATO security through science series. Human and societal dynamics, 2005)
Aims to show how community-based psychosocial approaches promote the psychosocial well being of children following war and terrorism. This book focuses on community-based interventions that link individual mental health/psychosocial well being with the health and stability of the community.